A comparison of energy stock return models using Pitman closeness criterion. (1st January 2014) - Pennywell, Gwendolyn; Chow, Alan; Javine, Victoria
This paper compares the performance of stock return models for firms in the energy and various other industries. Using Pitman closeness criterion, we evaluate the performance of several popular pricing models, in an effort to determine if one outperforms the others. Consistent with previous literature, a review of the models and their performance over time, indicate that the Fama–French three–factor model and the Carhart four–factor models alternate as better predictors of cross–sectional stocks returns. When the study is restricted to more recent data, the Carhart model outperforms the other models for more portfolios. Additionally, by using a shock in the energy industry, we found that the model choice is indeed sensitive to the industry.